2020
DOI: 10.3386/w27885
|View full text |Cite
|
Sign up to set email alerts
|

State Investment in Higher Education: Effects on Human Capital Formation, Student Debt, and Long-term Financial Outcomes of Students

Abstract: Most public colleges and universities rely heavily on state financial support. As state budgets have tightened in recent decades, appropriations for higher education have declined substantially. Despite concerns expressed by policymakers and scholars that the declines in state support have reduced the return to education investment for public sector students, little evidence exists that can identify the causal effect of these funds on long-run outcomes. We present the first such analysis in the literature usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Relying on the state legislature for any or all budget resources (Romano & Palmer, 2016) makes community colleges resource dependent (Pfeffer & Salancik, 1978, 2003) requiring engagement in the political process (Lorenzo, 2018). Community college resource dependence is exacerbated by potential competition with universities for limited state discretionary budget resources (Chakrabarti et al., 2020; Lorenzo, 2018).…”
Section: Resource Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…Relying on the state legislature for any or all budget resources (Romano & Palmer, 2016) makes community colleges resource dependent (Pfeffer & Salancik, 1978, 2003) requiring engagement in the political process (Lorenzo, 2018). Community college resource dependence is exacerbated by potential competition with universities for limited state discretionary budget resources (Chakrabarti et al., 2020; Lorenzo, 2018).…”
Section: Resource Dependencymentioning
confidence: 99%
“…Though community colleges appear to underperform in some completion metrics, strong evidence exists of the benefits of state investment. The National Bureau of Economic Research (NBER) reports state investment in 2‐year colleges led to increases in educational attainment, lower likelihood of student loan debt delinquency and default, more car and home ownership, and improved upward social mobility (Chakrabarti et al., 2020). The NBER stresses the importance of state appropriations for realizing state attainment increases (Chakrabarti et al., 2020, p. 35).…”
Section: Resource Dependencymentioning
confidence: 99%
“…Schools can respond to such a budget shock in one of two ways: cut spending or raise revenue. Recent work has found that between 30 percent and 60 percent of a reduction in state appropriations is passed through to students in the form of higher tuition (Webber 2017; Chakrabarti, Gorton, and Lovenheim 2020). While higher tuition might be a more visible harm to students, Deming and Walters (2017) conclude that reductions in spending resulting from these budget shocks are actually more damaging to students as they lead to lower graduation rates.…”
Section: The Institutional Landscapementioning
confidence: 99%
“…For example, financial support from the government to various education institutions helps in serving students from disadvantaged backgrounds and low-income households which can further help in reducing income inequalities. The state appropriation or spending by the government has positive short-run as well as long-run effects on students’ outcomes (Chakrabarti et al, 2020). Chakrabarti et al (2020) suggest that schools serving students from the lower-income groups are mostly affected by state expenditure cuts, which further lead to rising inequalities and poor student outcomes.…”
Section: Poverty Human Development and Public Expenditurementioning
confidence: 99%
“…The state appropriation or spending by the government has positive short-run as well as long-run effects on students' outcomes (Chakrabarti et al, 2020). Chakrabarti et al (2020) suggest that schools serving students from the lower-income groups are mostly affected by state expenditure cuts, which further lead to rising inequalities and poor student outcomes. The study also finds that an increase in the state spending leads low-income background students to benefit more, have better credit scores in future with lower rates of debt defaults, and achieve better living condition in more affluent areas by the age of 35.…”
Section: Direct Policy Measuresmentioning
confidence: 99%